Sex moderates the association between age and myelin water fraction in the cingulum and fornix among older adults without dementia - Brenner, Einat K.; Bangen, Katherine J.; Clark, Alexandra L.; Delano-Wood, Lisa; Evangelista, Nicole D.; Edwards, Lauren; Sorg, Scott F.; Jak, Amy J.; Bondi, Mark W.; Deoni, Sean C. L.; Lamar, Melissa (Frontiers in Aging Neuroscience, 2023)
Background Decreasing white matter integrity in limbic pathways including the fornix and cingulum have been reported in Alzheimer’s disease (AD), although underlying mechanisms and potential sex differences remain understudied. We therefore sought to explore sex as a moderator of the effect of age on myelin water fraction (MWF), a measure of myelin content, in older adults without dementia (N = 52). Methods Participants underwent neuropsychological evaluation and 3 T MRI at two research sites. Multicomponent driven equilibrium single pulse observation of T1 and T2 (mcDESPOT) quantified MWF in 3 a priori regions including the fornix, hippocampal cingulum (CgH), and cingulate cingulum (CgC). The California Verbal Learning Test-Second Edition assessed learning and delayed recall. Multiple linear regressions assessed for (1) interactions between age and sex on regional MWF and (2) associations of regional MWF and memory. Results (1) There was a significant age by sex interaction on MWF of the fornix (p = 0.002) and CgC (p = 0.005), but not the CgH (p = 0.192); as age increased, MWF decreased in women but not men. (2) Fornix MWF was associated with both learning and recall (ps < 0.01), but MWF of the two cingulum regions were not (p > 0.05). Results were unchanged when adjusting for hippocampal volume. Conclusion The current work adds to the literature by illuminating sex differences in age-related myelin decline using a measure sensitive to myelin and may help facilitate detection of AD risk for women.